Exogenous putrescine attenuates the negative impact of drought stress by modulating physio-biochemical traits and gene expression in sugar beet (Beta vulgaris L.) - Islam, Md Jahirul; Uddin, Md Jalal; Hossain, Mohammad Anwar; Henry, Robert; Begum, Mst. Kohinoor; Sohel, Md. Abu Taher; Mou, Masuma Akter; Ahn, Juhee; Cheong, Eun Ju; Lim, Young-Seok (PloS one, 2022)
Drought tolerance is a complex trait controlled by many metabolic pathways and genes and identifying a solution to increase the resilience of plants to drought stress is one of the grand challenges in plant biology. This study provided compelling evidence of increased drought stress tolerance in two sugar beet genotypes when treated with exogenous putrescine (Put) at the seedling stage. Morpho-physiological and biochemical traits and gene expression were assessed in thirty-day-old sugar beet seedlings subjected to drought stress with or without Put (0.3, 0.6, and 0.9 mM) application. Sugar beet plants exposed to drought stress exhibited a significant decline in growth and development as evidenced by root and shoot growth characteristics, photosynthetic pigments, antioxidant enzyme activities, and gene expression. Drought stress resulted in a sharp increase in hydrogen peroxide (H 2 O 2 ) (89.4 and 118% in SBT-010 and BSRI Sugar beet 2, respectively) and malondialdehyde (MDA) (35.6 and 27.1% in SBT-010 and BSRI Sugar beet 2, respectively). These changes were strongly linked to growth retardation as evidenced by principal component analysis (PCA) and heatmap clustering. Importantly, Put-sprayed plants suffered from less oxidative stress as indicated by lower H 2 O 2 and MDA accumulation. They better regulated the physiological processes supporting growth, dry matter accumulation, photosynthetic pigmentation and gas exchange, relative water content; modulated biochemical changes including proline, total soluble carbohydrate, total soluble sugar, and ascorbic acid; and enhanced the activities of antioxidant enzymes and gene expression. PCA results strongly suggested that Put conferred drought tolerance mostly by enhancing antioxidant enzymes activities that regulated homeostasis of reactive oxygen species. These findings collectively provide an important illustration of the use of Put in modulating drought tolerance in sugar beet plants.